ANALISIS EFEKTIFITAS IMPLEMENTASI TATA KELOLA (CORPORATE GOVERNANCE) PADA PERUSAHAAN PT PERUSAHAAN GAS NEGARA TBK - Halimatussya'diah,; Eko Rivandi Mulyana,; Christiven Manaek,; Christiven Aldina,; Alifvia Aisy Kurniawan,
PT Perusahaan Gas Negara Tbk is a company that is the main provider of natural gas and has two business fields, namely distribution or sale of natural gas and transmission of natural gas transportation through pipelines spread throughout the business area. The case that we take from PGN has clearly violated the principles of corporate governance, especially the principles of transparency, fairness, and responsibility. Namely a violation of the principles of transparency of information about project delays and a decrease in gas volume. PT Perusahaan Gas Negara Tbk. The absence of delays in submitting corrected information on the planned reduced gas volume and covering up pending problems from the project that should have been carried out caused the company's insiders to carry out Insider Trading. Keywords: Corporate Governance, Boards, Bapepam LK